Confessions under Malaysian and Islamic law: A comparative evaluation - Shair Mohamad, Mohd Akram (INSI Publications, 2012)
A valid confession is the most valuable and reliable evidence in the possession of the prosecution. This is especially where the available circumstantial evidence is not cogent and compelling in such a way as to link the accused to with the commission of the crime. Consequently, the law enforcement agents usually try to get a confession of the accused to prove their cases. Many methods are thus used to retrieve such evidence including but not limited to coercion. However, what amounts to confessions is not that an easy task. The court plays an important such in the admissibility of confessions. Based on this, the makes a comparative evaluation of confessions under the Malaysian and Islamic law perspectives. It uses many case laws, verses of the Qur’an and Sunnah of the Prophet (s.a.w.) and opinions of scholars to make the legal evaluation. It finds that though both systems have different approaches to confessions, the hallmark of admissibility of confessions in the two systems is its voluntariness.